Letter from William Randolph Hearst to Julia Morgan, March 11, 1921 - William Randolph Hearst::::::author::: (1921)
William Randolph Hearst describes the Italian velvet, Renaissance tapestries, and Renaissance stalls he plans to have used in House C and the main building